Rheumatoid Arthritis 2022
DOI: 10.5772/intechopen.99133
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanisms of Antirheumatic Herbal Medicines

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory and debilitating joint disorder that causes severe impairment and reduces the quality of life. The available synthetic medicines used as standard therapy for RA have numerous side effects that can compromise their therapeutic outcomes. Thus, the demand for alternative and complementary medicines is increasing. A search of English articles in PubMed, Scopus, Google Scholar, and Web of Science databases was carried out on probable mechanisms of action of herbs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The medicinal advantages of several types of rosemary extracts and their main chemical components, such as rosmarinic acid, carnosol, and carnosic acid have attracted increasing scientific interest in recent years. Numerous studies have shown that rosemary and its compounds have a wide range of therapeutic benefits, including anti‐inflammatory (Rahbardar et al, 2017), antinociceptive (Ghasemzadeh et al, 2016), antioxidant (Nakisa & Ghasemzadeh, 2022; Rahbardar et al, 2018), antiapoptotic (Ghasemzadeh et al, 2016), antidote (Alavi et al, 2021), antirheumatic (Nakisa & Rahbardar, 2022), antidepressant (Rahbardar & Hosseinzadeh, 2021), cardioprotective (Ghasemzadeh Rahbardar et al, 2024; Rahbardar et al, 2022), and neuroprotective effects (Ghasemzadeh Rahbardar et al, 2022; Ghasemzadeh Rahbardar & Hosseinzadeh, 2020).…”
Section: Herbal Sleep‐inducing Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The medicinal advantages of several types of rosemary extracts and their main chemical components, such as rosmarinic acid, carnosol, and carnosic acid have attracted increasing scientific interest in recent years. Numerous studies have shown that rosemary and its compounds have a wide range of therapeutic benefits, including anti‐inflammatory (Rahbardar et al, 2017), antinociceptive (Ghasemzadeh et al, 2016), antioxidant (Nakisa & Ghasemzadeh, 2022; Rahbardar et al, 2018), antiapoptotic (Ghasemzadeh et al, 2016), antidote (Alavi et al, 2021), antirheumatic (Nakisa & Rahbardar, 2022), antidepressant (Rahbardar & Hosseinzadeh, 2021), cardioprotective (Ghasemzadeh Rahbardar et al, 2024; Rahbardar et al, 2022), and neuroprotective effects (Ghasemzadeh Rahbardar et al, 2022; Ghasemzadeh Rahbardar & Hosseinzadeh, 2020).…”
Section: Herbal Sleep‐inducing Medicinesmentioning
confidence: 99%
“…Numerous studies have shown that rosemary and its compounds have a wide range of therapeutic benefits, including anti-inflammatory (Rahbardar et al, 2017), antinociceptive (Ghasemzadeh et al, 2016), antioxidant (Nakisa & Ghasemzadeh, 2022;Rahbardar et al, 2018), antiapoptotic (Ghasemzadeh et al, 2016), antidote (Alavi et al, 2021), antirheumatic (Nakisa & Rahbardar, 2022), antidepressant , cardioprotective Rahbardar et al, 2022), and neuroprotective effects (Ghasemzadeh Rahbardar et al, 2022;Ghasemzadeh Rahbardar & Hosseinzadeh, 2020).…”
Section: Rosmarinus Officinalis (Rosemary)mentioning
confidence: 99%
“…The phenolic acids, phenolic diterpenes, and phenolic triterpenes are the components of Rosemary officinalis that are most potent. According to phytochemical analysis, Rosemary has alkaloids, flavonoids, terpenoids, and essential oil [101][102][103][104]. Many illnesses, such as stomachaches, headaches, rheumatoid arthritis, and memory loss, have been managed and treated using Rosemary bioactive [105].…”
Section: Chemical Constituentmentioning
confidence: 99%
“…Turmeric is used in traditional medicine to treat liver and respiratory disorders, allergies, sinusitis, and anorexia (Razavi et al, 2021). At present, this herb is also known to have antirheumatic (Nakisa & Rahbardar, 2021), anti‐cancer (Gurer et al, 2022), antidotal (Ara et al, 2020; Hosseini & Hosseinzadeh, 2018), anti‐hypertriglyceridemia (Mollazadeh et al, 2019), hypoglycemic (El‐Hadary & Sitohy, 2021), anti‐depressive (Alavi et al, 2021), hepatoprotective, anti‐obesity (Vafaeipour et al, 2022), cardioprotective (Akhter & Nahar, 2022), and anti‐microbial (Soleimani et al, 2018) effects. Additionally, turmeric has been shown to have anti‐inflammatory (Liu et al, 2022), antioxidant (Adab et al, 2019), and anti‐apoptotic (Ibrahim et al, 2019) effects in numerous studies.…”
Section: Introductionmentioning
confidence: 99%